2013
DOI: 10.1007/s12035-013-8514-7
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Normalizes Caspase 3, Synaptophysin, and Mitochondrial Fission Protein DNM1L Expression Levels in Rats with Brain Iron Overload: Implications for Neuroprotection

Abstract: We have recently shown that chronic treatment with cannabidiol (CBD) was able to recover memory deficits induced by brain iron loading in a dose-dependent manner in rats. Brain iron accumulation is implicated in the pathogenesis of neurodegenerative diseases, including Parkinson's and Alzheimer's, and has been related to cognitive deficits in animals and human subjects. Deficits in synaptic energy supply have been linked to neurodegenerative diseases, evidencing the key role played by mitochondria in maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 59 publications
4
59
0
1
Order By: Relevance
“…We have previously described that iron overload induces severe and persistent long-term impairments in spatial, recognition, and emotional memories 511 . In molecular analyses, we found lipid peroxidation and oxidative damage associated with iron excess 6 , increased apoptotic markers, Par4 12 and Caspase 3 13 , accumulation of ubiquitinated proteins 14 , and reactive gliosis 15 . Moreover, iron treatment in the neonatal period decreased acetylcholinesterase activity in the striatum 8 and affected the regulation of iron homeostasis proteins in the hippocampus, cortex, and striatum of aged rats 16 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We have previously described that iron overload induces severe and persistent long-term impairments in spatial, recognition, and emotional memories 511 . In molecular analyses, we found lipid peroxidation and oxidative damage associated with iron excess 6 , increased apoptotic markers, Par4 12 and Caspase 3 13 , accumulation of ubiquitinated proteins 14 , and reactive gliosis 15 . Moreover, iron treatment in the neonatal period decreased acetylcholinesterase activity in the striatum 8 and affected the regulation of iron homeostasis proteins in the hippocampus, cortex, and striatum of aged rats 16 .…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, iron treatment in the neonatal period decreased acetylcholinesterase activity in the striatum 8 and affected the regulation of iron homeostasis proteins in the hippocampus, cortex, and striatum of aged rats 16 . In addition, there was a decrease in synaptophysin levels, a marker of synaptic viability, and changes in DNM1L levels, a protein critically involved in mitochondrial dynamics in the hippocampus of iron-treated rats 13 . We have also demonstrated that iron chelation prevented memory impairments and oxidative stress in aged rats, supporting the concept that cognitive deficits associated with aging might be related to iron accumulation in the brain 17 .…”
Section: Introductionmentioning
confidence: 97%
“…This led to further investigations on the anticonvulsant action first of extracts and then of isolated compounds of the plant (111, 212,275,276,280) and almost simultaneously to effects of Cannabis and its compounds on fear learning (212,275,288,467) in the laboratory of E. A. Carlini in São Paulo. Concerning the anticonvulsant effects, the nonpsychotropic natural cannabinoid cannabidiol is now beginning to draw generalized attention through a variety of effects aside from the anticonvulsant one: anxiolytic (67) and perhaps neuroprotective (161,600). Concerning the anxiolytic effect, recent studies show that cannabidiol acting on the PL vmPFC via 5HT 1A receptor-mediated mechanisms can be anxiolytic or anxiogenic in an elevated plus maze depending on the previous record of the animals in terms of stressful experiences (174,387).…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Previous studies in rodents have shown that oral administration of iron during the period of rapid brain development produces iron accumulation in the hippocampus. Da Silva et al [12] observed that iron-induced oxidative stress may be related to mitochondrial dysfunction, resulting in an alteration in the expression of fusion and fission proteins, which might ultimately lead to unbalanced mitochondrial dynamics and impaired energy production reducing the ATP levels in the brain of rats [12]. The impairment of mitochondrial function and reduction of ATP levels and extracellular adenosine accumulation are pathological conditions found in neurodegenerative diseases such as Alzheimer's disease (AD), which is closely linked to the decline of cognitive processes [13].…”
Section: Introductionmentioning
confidence: 99%